2014
DOI: 10.1177/1470320314551443
|View full text |Cite
|
Sign up to set email alerts
|

Urinary angiotensin-converting enzyme 2 increases in diabetic nephropathy by angiotensin II type 1 receptor blocker olmesartan

Abstract: Introduction: Angiotensin-converting enzyme 2 (ACE2) is a member of the renin–angiotensin system that degrades angiotensin (Ang) II to the seven-amino acid peptide fragment Ang-(1-7). We evaluated the changes in urinary ACE2 levels in response to treatment with the angiotensin II type 1 receptor blocker olmesartan in diabetes patients with nephropathy. Materials and methods: This prospective, open-label, interventional study was conducted with 31 type 2 diabetes patients with nephropathy. After initial evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Increased urinary L-FAbP levels may occur in response to oxidative stress induced by hypoxia, which is a pathogenetic factor underlying diabetic complications such as nephropathy [31][32][33][34]. Urinary L-FAbP is an important marker of tubulointerstitial changes in diabetic nephropathy, while oxidative stress is a pathogenetic factor underlying diabetic complications such as nephropathy [32][33][34][35]. Therefore, the present data suggest that ACE2 is an endogenous protector against the progression of tubulointerstitial damage since multivariate regression analysis showed that urinary L-FAbP is an independent variable significantly associated with urinary ACE2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased urinary L-FAbP levels may occur in response to oxidative stress induced by hypoxia, which is a pathogenetic factor underlying diabetic complications such as nephropathy [31][32][33][34]. Urinary L-FAbP is an important marker of tubulointerstitial changes in diabetic nephropathy, while oxidative stress is a pathogenetic factor underlying diabetic complications such as nephropathy [32][33][34][35]. Therefore, the present data suggest that ACE2 is an endogenous protector against the progression of tubulointerstitial damage since multivariate regression analysis showed that urinary L-FAbP is an independent variable significantly associated with urinary ACE2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reported that the administration of telmisartan, an angiotensin II receptor antagonist (ARB), led to a reduction of the urinary L-FABP level in the patients with diabetic nephropathy [ 35 , 36 ]. It was also demonstrated that the administration of olmesartan [ 37 ], another ARB, lisinopri [ 38 ], an angiotensin-converting enzyme inhibitor, and azelnidipine [ 39 ], a calcium channel blocker, reduced the level of urinary L-FABP in patients with type 2 diabetes. Thus, although the changes in systolic blood pressure were not found to be associated with the changes in urinary L-FABP in the present study, the reduction in urinary L-FABP may be caused by the control of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…DISEQUILIBRIUM OF RAS IN SARS-CoV-2-RELATED LUNG INJURY ACE, abundant in lung tissue, consisting of an extracellular NH 2 -terminal domain containing a catalytic site and intracellular COOH-terminal tail. ACE2 has many peptides as substrates, but mainly cleaves Ang I into a nonapeptide [Ang (1)(2)(3)(4)(5)(6)(7)(8)(9)] that binds AT 2 R and Ang II into a heptapeptide [Ang(1-7)] that binds an endogenous orphan receptor (Mas receptor, MasR) ( Fig. 2A, top) (73).…”
Section: L327mentioning
confidence: 99%